2014
DOI: 10.1080/08927014.2014.981165
|View full text |Cite
|
Sign up to set email alerts
|

In siturheology of yeast biofilms

Abstract: The aim of the present work was to investigate the in situ rheological behavior of yeast biofilms growing on stainless steel under static and turbulent flow. The species used (Rhodototula mucilaginosa, Candida krusei, Candida kefyr and Candida tropicalis) were isolated from a clarified apple juice industry. The flow conditions impacted biofilm composition over time, with a predominance of C. krusei under static and turbulent flow. Likewise, structural variations occurred, with a tighter appearance under dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Candida tropicalis L5, a strain previously isolated from UF membranes, strongly adheres to the surface of stainless steel, forming resistant biofilms which may confer a competitive advantage over other yeasts (Brugnoni et al . ; Tarifa et al . , ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Candida tropicalis L5, a strain previously isolated from UF membranes, strongly adheres to the surface of stainless steel, forming resistant biofilms which may confer a competitive advantage over other yeasts (Brugnoni et al . ; Tarifa et al . , ).…”
Section: Introductionmentioning
confidence: 99%
“…Yeasts predominate among microbial communities as spoilage micro-organisms, particularly in acidic food products like apple juice, due to their ability to grow at low pH, high sugar concentration and low water activity conditions, and to resist inactivation by heat processing isolated from UF membranes, strongly adheres to the surface of stainless steel, forming resistant biofilms which may confer a competitive advantage over other yeasts (Brugnoni et al 2014;Tarifa et al 2013Tarifa et al , 2015. As cleaning procedures cannot easily remove yeast in such sites (Brugnoni et al 2012;Tarifa et al 2013), it was assumed that this community is able to persist over time on food production surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Brugnoni et al ( 2007 , 2011 ) found that C. krusei isolated from a large-scale apple juice processing plant was capable of rapidly colonizing and covering stainless steel surfaces. Moreover, C. krusei was found in mixed biofilms subjected to varying hydrodynamic conditions commonly found in apple juice facilities (Brugnoni et al 2014 ). Of particular significance, C. krusei biofilm was identified as potentially playing an important role in the survival and dissemination of Escherichia coli O157:H7 and Salmonella enterica in food-processing environments (Tarifa et al 2017 ).…”
Section: Yeast Biofilm In Food Realmsmentioning
confidence: 99%
“…The mechanical properties of biofilms from Rhodotorula mucilaginosa , Candida krusei , Candida kefyr and Candida tropicalis were examined with a focus on industrial applications. Essentially, yeast biofilms of these species were determined to be viscoelastic materials with a solid-like behavior ( Brugnoni et al, 2014 , Tarifa et al, 2017 ).…”
Section: Extracellular Matrix and Microbial Biofilmmentioning
confidence: 99%